Research on the Influence of Overseas M&A on the Service Oriented Transformation of Manufacturing Enterprises From the Perspective of Resource Quality - Can Zhao, Jie Gao (Forest Chemicals Review)
Based on the 148 M&A samples of listed Chinese manufacturing companies from 2001 to 2018, this study demonstrates from an empirical perspective the feasibility for manufacturing companies to realize service-oriented transformation through overseas M&A. Research shows that overseas M&A can improve the servitization level of manufacturing enterprises, and the resource local stickiness of target enterprises can significantly enhance this improvement; Further study on the influence of industry heterogeneity found that in industries with slow industrial clock speed, the quality of M&A resources has a stronger positive effect on the servitization of manufacturing industry. However, the promotion of service-oriented level brought by M&A does not significantly improve the enterprise performance. This may be related to the “time lag effect” or the management level after M&A. The study reveals the mechanism through which overseas M&A facilitates the leapfrog development of servitization of manufacturing industry and the improvement of corporate performance, summarizes the unique model of China’s manufacturing enterprises to achieve service-oriented transformation, and proposes a universal approach for manufacturers in emerging economies to achieve sustainable growth and move upstream of the industrial chain.